MICROCLIMATIC CHARACTERIZATION OF CONILON COFFEE CULTIVATED IN NORTH-SOUTH ALIGNMENT IN NORTHEN ESPÍRITO SANTO STATE, BRAZIL - Bis, Ana Paula Pereira; Partelli, Fábio Luiz; Rodrigues, Weverton Pereira; Falqueto, Antelmo Ralph; Espindula, Marcelo Curitiba; Martins, Lima Deleon (Coffee Science - ISSN 1984-3909, 2019)
The objective in this work was to study the influence of the North-South plantation alignment with respect to microclimatic, growth, and mineral nutrition conditions in order to quantify the variables and to point out possible consequences for the coffee tree. The experiment was carried out in a 6-year-old conilon coffee (Coffea canephora) crop with a mean height of 1.6 m, cultivated in full sun and spaced 3.5 m x 1.0 m. The data were collected on four dates from December 2016 to September 2017 in North Espírito Santo State, Brazil. The irradiance, air temperature, and vapor pressure deficit variables were quantified by means of external data loggers. The leaf temperature was determined by means of thermal images, and the plant growth and nutrient concentration in the leaves on both sides of the plant (East and West) were evaluated. The West side of the plant showed higher values of irradiance, temperature, and vapor pressure deficit in the afternoon, reaching a difference of 5°C between the two sides. The leaf temperature had similar behavior to air temperature, reaching a difference of approximately 12°C between the two sides in the afternoon. Although significant differences were observed for some nutrients between the sides of the plant, macro and micronutrient leaf contents remained within the range considered adequate for the coffee tree.